Corrosion Behaviour of Additive Manufactured Metals - Özer, Gökhan; Yılmaz, Mustafa Safa (Springer, 2023)
Additive manufacturing is the production process in which a 3D CAD model is combined into layers, and the material is turned into a physical part. Additive manufacturing is an important technology that is very popular and expected to take a more important place in our future lives. Additive manufacturing is a revolutionary method in automotive, aviation, aerospace, health construction, and energy. Therefore, understanding additive manufacturing technology is a very strategic issue for today. Corrosion is the phenomenon of metal or metal alloys being damaged by oxidation or other chemical effects. Corrosion is the most harmful type of damage in parts working in the industry today, corrosion studies of metal parts (such as aluminum, maraging steel, stainless steel, and titanium) are essential. Therefore, if additive manufacturing technologies want to find widespread application, corrosion behavior should be considered. Additive manufacturing parts have a unique microstructure. This microstructure affects the corrosion behavior of the parts. Hence, corrosion behavior of metallic parts produced by additive manufacturing becomes a more important field. This section will explain the corrosion behavior and protection methods of important metal alloys produced by additive manufacturing.